Microfluidic transection injury and high-shear thrombus formation demonstrate increased hemostatic efficacy of cold-stored platelets and in vitro resuscitation in induced coagulopathy models - Mihalko, Emily P.; Munitz, Refael; Dishong, Devin M.; Clayton, Skye; Shea, Susan M. (Frontiers in Bioengineering and Biotechnology, 2025)
Hemostatic resuscitation is an essential aspect of treating traumatic bleeding. Trauma-induced coagulopathy is a multifactorial disorder that can lead to increased transfusion requirements. However, little is known about the interplay between coagulopathies and stored blood products used for hemostatic resuscitation, which themselves acquire dysfunction in the form of a storage lesion. Physiologically relevant models can aid in the study of trauma and hemostatic resuscitation by incorporating important aspects such as biological surfaces and flow regimes that mimic injury. This study aims to evaluate the contribution of platelet products under varying storage conditions in coagulopathic states. This study utilized microfluidic platforms of high shear, a flow regime relevant to injury, including a stenotic straight channel and a severe transected vessel injury device. Apheresis platelet products were collected from healthy volunteers, stored at room temperature (RT) or cold-stored (CS) (1°C–6°C), and tested for product cell count and intrinsic product function in a high-shear stenotic microfluidic device across storage days (D2, D5, and D7 for RT; D2, D5, D7, D14, and D21 for CS). Hemostatic resuscitation efficacy of products was assessed using induced coagulopathy models of dilution and thrombocytopenia (TP). In vitro hemostatic resuscitation was assessed in both the stenotic straight channel for kinetic platelet contributions and the transected-vessel injury device, using blood loss and clot composition as endpoints. CS products conserved inherent function despite decreasing platelet counts through storage D7. When mixed with coagulopathic blood, D2 RT products did not show hemostatic benefit in the dilutional coagulopathy (DC) model. However, both D2 RT and CS showed hemostatic benefits in the thrombocytopenia model. CS products (D5 and D7) also showed an enhanced ability to recruit recipient platelets in the thrombocytopenia model compared to RT. Overall, this study highlights disparate responses associated with product storage duration and temperature, indicating the need to further evaluate hemostatic resuscitation efficacy under flow in pathologically relevant models to guide transfusion practices.